Neurocritical Care Management of Hepatic Encephalopathy and Coma in Liver Failure - Kerbert, Annarein J.; Engelmann, Cornelius; Jalan, Rajiv (Seminars in Respiratory and Critical Care Medicine, 2018)
Hepatic encephalopathy (HE) is a severe complication of liver disease, describing a spectrum of neurological and psychiatric abnormalities ranging from subclinical alterations to coma. HE is the leading cause for hospital readmission, intensive care treatment, and mortality in patients with chronic liver disease. The complex and multifaceted pathogenesis is not yet fully understood, but hypotheses focus on ammonia and systemic inflammation, which are the main targets for currently available therapies in clinical practice. Nevertheless, the remaining high clinical relevance and healthcare burden of this syndrome underlines the emergence for further unraveling the full spectrum of pathomechanisms, as this provides the basis for the development of novel, highly targeted therapies. In this review, the most recent literature about current and future therapies for HE, relevant for intensive care management, will be discussed.
Keywords: hepatic encephalopathy; pathogenesis; classification; diagnosing; treatment